Characterization of novel type I ribosome-inactivating proteins isolated from oil palm (Elaeis guineensis) inoculated with Ganoderma boninense, the causal agent of basal stem rot - Sargolzaei, Maryam; Ho, Chai Ling; Wong, Mui Yun (Elsevier, 2016)
Type I RIPs have not been identified in oil palm. EgRIP-1a and EgRIP-1b transcripts were partially isolated from roots and basal stems of oil palm seedlings with high similarity to type I RIPs. Expression levels were altered during plant-pathogen interaction and their proteins were 28–30 kD with an estimated pI value of 10.0. Depurination of yeast 26S rRNA by EgRIP proteins demonstrated specific ribosome-inactivating activity. EgRIP proteins showed inhibition on G. boninense mycelial growth with 44.1% at 5 DAI. It was concluded that the novel EgRIPs are type I and demonstrated to have antifungal effect against G. boninense.